Optimizing International Joint Venture (IJV) Ownership Structures: A Technology and Knowledge Transfer-Linked Productivity Growth Perspective - Wollenberg, Alexander (2013)
This chapter portrays a quantitative framework regarding entry mode choice and ownership structures by measuring performance under given ownership structures as the degree of efficiency in technology transfer, and knowledge exchange in the form of a residual productivity growth variable. This method has been shown to be a proxy for or an indirect measure of transaction costs, in that ownership structures are validated by the growth in technology/knowledge-based productivity that they caused. In the process, the chapter discusses hierarchical entry modes and adjustment of ownership structures with respect to minimizing transaction costs incurred in the transfer and internalization of complementary assets, both tangible and intangible. Previous research has dealt with subsidiary performance mainly in terms of financial measures (e.g., profitability, ROA, ROE, ROI), instability, and lifespan. By contrast, this chapter extends existing research by providing a specific quantitative framework for optimizing technology/knowledge-based productivity growth. The second important contribution of the chapter is the linkage of the quantitative results to their applicability and potential for implementation in Japanese equity-based subsidiaries in Latin America over the lifetime of the subsidiaries. Other factors important in the implementation and internalization of new technologies and knowledge have also been analyzed quantitatively and linked to case studies qualitatively.The chapter further analyzes adaptations to regional contexts and parent companies of nationalities other than Japanese. Therefore, the model presented in the chapter addresses IJV ownership structures which are optimal to productivity growth linked to new technologies and knowledge and by adaptation of variables, and discusses results for emerging markets in Latin America, such as Peru, Colombia, and the newly industrialized Brazil. The chapter also highlights advantages and disadvantages of forming IJVs with a local partner of different levels of technological sophistication, and the degree of managerial and equity involvement to allow the local partner.